The differences between functional assignees and developmental assignees in terms of expatriation management practices and determinants of turnover intention - Xia, Mengzhao (My University, 2013)
This study reviews the distinction between functional assignees and developmental assignees on the availability of expatriation management practices given by the organization. In addition, this study compares the differences between functional assignees and developmental assignees on job related factors such as perceived organizational support, organizational commitment, career advancement, perception of underemployment, and perceived career advancement opportunity from employee’s perspective. Moreover, the study investigates the determinants of turnover intention. Quantitative method is adopted in this study. In particular, regression and descriptive statistics are used. The results of a study of 68 repatriates from various corporations suggest that there is no significant difference between different types of assignees with regard to repatriation practices, perceived organizational support, career advancement, perceived underemployment, and perceived career advancement opportunity. In addition, the study justifies independent variables: perceived organization support, organizational commitment, career advancement, perceived underemployment, and perceived career advancement opportunity all have an influence on employee’s turnover intention. Besides, the study finds repatriation concerns, employability, and turnover intention differs from functional assignees and developmental assignees. The findings of the study contribute to the understanding of repatriates’ difference in various job related factors. Furthermore, the study reveals the factors that have an effect on employee’s turnover intention. Organizations can improve expatriation management and prevent human capital loss by taken into account the difference between assignees and the factors that influence turnover intention.
Keywords: Expatriation; repatriation; assignees; turnover intention; retention; fi=Master's Degree Programme in International Business|